2021
DOI: 10.1590/1982-0224-2020-0082
|View full text |Cite
|
Sign up to set email alerts
|

The most important fishery resource in the Amazon, the migratory catfish Brachyplatystoma vaillantii (Siluriformes: Pimelodidae), is composed by an unique and genetically diverse population in the Solimões-Amazonas River System

Abstract: The migratory catfish Brachyplatystoma vaillantii is one of the most important fishery resources in the Amazon. Intense capture occurs associated to its life cycle. In order to know the genetic status, we sequenced the mitochondrial DNA control region from 150 individuals of B. vaillantii, collected in five fishing landing locations, covering the length of the Solimões-Amazonas River in Brazil. Genetic diversity parameters suggest there is no genetic differentiation between the five localities. Population’s ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…To date, a single stock of B . vaillantii has been identified in the Amazon Basin [ 11 ]. Genetic studies of B .…”
Section: Discussionmentioning
confidence: 99%
“…To date, a single stock of B . vaillantii has been identified in the Amazon Basin [ 11 ]. Genetic studies of B .…”
Section: Discussionmentioning
confidence: 99%
“…Harnessing population genetics has also disentangled the spatial scale at which migrations occur. Highly migratory species are associated with poor genetic structure, although some research has identified discrete populations among some of the longest migrants, such as Dourada ( Brachyplatystoma rousseauxii , Pimelodidae) (Carvajal‐Vallejos et al., 2014) and Piramutaba ( Brachyplatystoma vaillantii , Pimelodidae) (Formiga et al., 2021).…”
Section: Challenges and Opportunities For Advancing The Study Of Fish...mentioning
confidence: 99%
“…Te ecological function of the Siluriform order, more specifcally from the Pimelodidae family, and their inter-or intraspecifc interactions are fundamental for environmental balance [7][8][9]. Also known as "catfsh," they are responsible for dispersing seeds throughout the basin through zoochory, evidencing the important ecological role played by aquatic biota when using the fooded forests as habitat and source of food [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%